How does climate change affect a fishable resource? The case of the royal sea cucumber (Parastichopus regalis) in the central Mediterranean Sea - Scannella, Danilo; Bono, Gioacchino; Di Lorenzo, Manfredi; Di Maio, Federico; Falsone, Fabio; Gancitano, Vita; Garofalo, Germana; Geraci, Michele Luca; Lauria, Valentina; Mancuso, Maria; Quattrocchi, Federico; Sardo, Giacomo; et al. (Frontiers in Marine Science, 2022)
Holothurians or sea cucumbers are key organisms in marine ecosystems that, by ingesting large quantities of sediments, provide important ecosystem services. Among them, Parastichopus regalis (Cuvier, 1817) is one of the living sea cucumbers in the Mediterranean actively fished for human consumption mainly in Spain, where it is considered a gastronomic delicacy. In the Strait of Sicily (central Mediterranean Sea), this species is not exploited for commercial use even if it is used as bait by longline fishery. P. regalis is frequently caught by bottom trawling and discarded at sea by fishers after catch, and because of its capacity to resist air exposition (at least in cold months), it is reasonable to consider that it is not affected by fishing mortality. Having observed a significant decrease in abundance since 2018, the possible effects of some ecological factors related to current climate change (i.e., temperature and pH) were sought. Generalized additive models (GAMs) were applied to investigate the relationship among the abundance of P. regalis and environmental variables and fishing effort. Long time series of P. regalis densities (2008–2021) were extracted from the MEDITS bottom trawling survey and modeled as function of environmental parameters (i.e., salinity, dissolved oxygen, ammonium, pH, and chlorophyll α) and fishing effort (i.e., total number of fishing days per gross tonnage). Our results showed that this species prefers the soft bottoms (50–200 m) of the Adventure Bank and Malta Plateau, and its distribution changed over time with a slight deepening and a rarefaction of spatial distribution starting from 2011 and 2017, respectively. In addition, a positive relationship with pH concentration in surface waters during the larval dispersal phase (3-year lag before the survey) and nutrient concentration at sea bottom (1-year lag) has been found, suggesting that this species is sensitive to climate change and food availability. This study adds new knowledge about the population dynamics of an unexploited stock of P. regalis under fishing impact and environmental under climate change in fisheries management.